Late Cenozoic tectono‐stratigraphic sequences of the Crotone Basin: insights on the geodynamic history of the Calabrian arc and Tyrrhenian Sea. (17th May 2012) - Massari, F.; Prosser, G.
Abstract The Crotone Basin was generated in the late Cenozoic as a forearc basin of the Ionian arc‐trench system. New data are gained through detailed field mapping, high‐resolution stratigraphic analysis of a key area and examination of offshore well data and seismic reflection profiles. Major unconformities divide the basin fill into major sequences, which reveal a three‐stage internal organization thought to reflect geodynamic events of the Calabrian arc and backarc area closely. The first stage is characterized by extensional block faulting and uplift followed by rapid drowning during high subsidence and transtension in the basin along a major NNW‐ to NW‐striking fault system. This stage is interpreted to reflect resumption of rollback after an episode of slab tearing triggered by transitory docking of continental lithosphere in the trench. The initial uplift is inferred to reflect decoupling and rebound after the transitory coupling phase. The second stage is characterized by increased subsidence and continued extension/transtension. This trend presumably reflects a decreasing rate of rollback resulting from a tendency towards viscous coupling after acceleration of slab downwelling. The third stage is characterized by short‐lived transpression along major shear zones and local inversion of former basins. This is inferred to reflect entrance into the trench of buoyant continental lithosphere, resulting in significant deceleration of slab rollback and consequently a break in, or slowing of, backarc extension, and predominance of the effects of compression related to Africa–Europe convergence. Overall, the above evolution resulted in the formation of a progressively narrower and rapidly retreating slab, inducing extreme rates of backarc extension, and may have played a critical role in determining the intermittent nature of the backarc rifting.